The Effects of Interest Rate, Household Consumptions, MSME Loans, and Domestic Investment Realization on GDP From 2011 to 2021 - Tri Wibowo, Mohamad Rafif; Devia, Vietha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Economic growth is a crucial indicator for assessing a country's development success, with Gross Domestic Product (GDP) serving as its benchmark. Fluctuations in Indonesia's GDP over the last decade have been influenced by various factors, including interest rates, household consumption, MSME loans, and domestic investment realization. This research aims to analyses the impact of these four variables on Indonesia's GDP from 2011 to 2021. The study uses a quantitative approach with multiple linear regression, drawing on secondary data from BPS (Statistics Indonesia), Bank Indonesia, and BKPM (Indonesia Investment Coordinating Board). The findings reveal that interest rates and MSME loans have a positive but not significant impact on GDP, while household consumption and domestic investment realization positively and significantly affect GDP. These results highlight the importance of boosting public consumption and realizing domestic investment as key strategies to accelerate national economic growth.